Assessing Students' Educational Needs for Virtual Cultural Exhibitions: A Case Study of South Sumatran Local Wisdom Integration via Artsteps in High School History Learning - Syarifuddin Syarifuddin; Suratmi Suratmi; Listen Prima; Siti Swasti Eka Dewie; Ayu Fadhilah; Elfira Rosa (STAI Hubbulwathan Duri, 2025)
The integration of local wisdom in digital learning is essential to preserve cultural identity among younger generations. However, history education in Indonesian high schools often lacks engaging and contextual media, resulting in low student interest and weak cultural attachment. This study investigates the educational needs of high school students for virtual cultural exhibitions incorporating South Sumatra’s local wisdom through the Artsteps platform. This preliminary study employed a mixed-method exploratory design involving 128 students from SMA LTI IGM Palembang. Data were collected through validated questionnaires comprising Likert-scale and open-ended items. Quantitative data were analyzed using descriptive statistics, while qualitative responses underwent thematic analysis. Findings reveal that 87% of students expressed strong needs for technology-based, flexible, and interactive learning media. YouTube (79.7%) and historical simulations (66.4%) were the most frequently used, but virtual tours were rarely accessed. Students showed high interest in features such as interactive quizzes (68%), traditional music backgrounds (68.8%), and 3D visualizations (62.5%). Local cultural elements most favored included historical figures (68.8%) and culinary traditions (68%). The results underscore the urgent need for immersive and culturally relevant learning innovations. Artsteps-based virtual exhibitions align well with students’ digital preferences and can foster deeper engagement with local history. The findings provide a strong foundation for developing virtual learning media that support cultural education and enhance historical understanding.